2007
DOI: 10.1080/01652176.2007.9695234
|View full text |Cite
|
Sign up to set email alerts
|

Pollakisuria in a dwarf goat due to pathologic enlargement of the uterus

Abstract: SUMMARYPollakisuria in adult goats can be caused by diseases of the urinary tract and by distension of parts of the genital tract leading to irritation of the bladder. Hydrometra is the most common cause of uterine distension in goats and usually can be resolved by prostaglandin injections. But other pathologies of the uterus can generate a similar syndrome. A dwarf goat was presented at the clinic with a history of chronic pollakisuria and tenesm. An initial ultrasonographic examination of the abdomen led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Pollakiuria and abdominal straining in goats with pathologic enlargement of the uterus has been reported, and is postulated to occur secondary to mechanical irritation of the urinary bladder. 1,8,12 The present case was also diagnosed with bilateral hydroureters secondary to compression of the ureters by uterine mass lesions, which may have contributed to this patient's abdominal straining.…”
Section: Research-article2017mentioning
confidence: 89%
“…Pollakiuria and abdominal straining in goats with pathologic enlargement of the uterus has been reported, and is postulated to occur secondary to mechanical irritation of the urinary bladder. 1,8,12 The present case was also diagnosed with bilateral hydroureters secondary to compression of the ureters by uterine mass lesions, which may have contributed to this patient's abdominal straining.…”
Section: Research-article2017mentioning
confidence: 89%
“…In the reproductive tract, the most common sites for leiomyoma formation are the uterus, vagina, and cervix [2]. Leiomyoma was diagnosed in the cervix in a 17-year-old Toggenburg doe with a history of acute vaginal bleeding and death [14]. The tumor was found to originate from the cervix and occupy most of the vaginal lumen [14].…”
Section: Discussionmentioning
confidence: 99%
“…Necropsy findings in this doe revealed that the metastatic adenocarcinoma originated from the uterus and infiltrated multiple abdominal organs. There are a couple of single case reports of uterine neoplasia of muscle origin in goats [13,14] and one report of metastasized adenocarcinoma of the uterus [15], but no case series of uterine neoplasia are described. Based on studies in other species [16], we may assume that they are more common in the geriatric population.…”
Section: Discussionmentioning
confidence: 99%